2008
DOI: 10.1021/la7039509
|View full text |Cite
|
Sign up to set email alerts
|

Pluronic Additives: A Solution to Sticky Problems in Digital Microfluidics

Abstract: Digital microfluidics (DMF) is a promising technique for carrying out miniaturized, automated biochemical assays in which discrete droplets of reagents are actuated on the surface of an array of electrodes. A limitation for DMF is nonspecific protein adsorption to device surfaces, which interferes with assay fidelity and can cause droplets to become unmovable. Here, we report the results of a quantitative analysis of protein adsorption on DMF devices by means of confocal microscopy and secondary ion mass spect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
191
2

Year Published

2009
2009
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 198 publications
(199 citation statements)
references
References 43 publications
5
191
2
Order By: Relevance
“…In all DMF experiments, reagent solutions were supplemented with 0.02% Pluronics F68 except for sol-state Geltrex and collagen that were supplemented with 0.02% Pluronics F127 (ref. 56). Imaging during droplet manipulation was performed with a built-in webcam 55 .…”
Section: Methodsmentioning
confidence: 99%
“…In all DMF experiments, reagent solutions were supplemented with 0.02% Pluronics F68 except for sol-state Geltrex and collagen that were supplemented with 0.02% Pluronics F127 (ref. 56). Imaging during droplet manipulation was performed with a built-in webcam 55 .…”
Section: Methodsmentioning
confidence: 99%
“…In the work reported here, protein sticking was controlled by the use of low concentrations of amphiphilic polymer additives (chapter 2). 128 In other contexts, we have observed that these additives have little or no effect on biochemical processes ranging from cell vitality 71 to enzyme kinetics, 72 and can prevent adsorption even in highly concentrated, heterogeneous solutions such as serum (chapter 2). 128 The combination of these strategies, that is, incubation in humidified chambers and the use of adhesion-reducing additives, facilitated the development of these digital microfluidic techniques.…”
Section: Multistep Proteomic Processing On Dmf Devicesmentioning
confidence: 99%
“…50,71,72,128 In each assay, fluorescence from processed samples was measured in intervals of 10 min for 1 h. Between intervals, devices containing the reacting droplets were stored in a humidified chamber to prevent evaporation. Three replicate trials were conducted for each condition, and data were normalized and fitted with exponential functions.…”
Section: Reaction Rate Analysismentioning
confidence: 99%
“…Encapsulation by immiscible oil is furthermore desired as it aids in controlling the rapid evaporation of nanoliter droplets. In a recent study, Luk et al 35 reported on the use of biocompatible polyethylene glycol ͑PEG͒ based additives in protein solutions to overcome biofouling on Teflon ® coated surfaces in electrowetting based microfluidic devices. 35 They showed that actuation of concentrated protein solutions ͑up to 50 mg/ml; bovine serum albumin ͑BSA͒, fibrinogen͒ is greatly facilitated ͑in air͒ by adding a small amount of PEG in protein solutions.…”
Section: Applicationsmentioning
confidence: 99%